The Concept of “Dance” and Its Word-forming Features in the Literary Armenian Language - Ghamoyan, Lusine (Bulletin of Yerevan University B: Philology, 2025)
This paper is an in-depth and detailed study covering the etymological and semantic features of the root “dance” in different periods of the Armenian language development, as well as the expression of its word-formation possibilities in the literary language. The study is conducted in two directions: diachronic analysis, which examines the semantic evolution of the notion of “dance”; and synchronic analysis of the parsing of compound words with this root. Special attention is paid to the nuances of the meaning of the root “dance”, its polysemy and semantic changes. Also neologisms containing the root “dance” are highlighted, which is important from the point of view of studying the lexical composition of the Armenian language.As research shows, the root of "dance" has not only preserved its ancient meanings, but has also been enriched with new ones, due to cultural and social changes.From the perspective of the genre, it exhibits great diversity, being the basis of many familiar, complex and expressive genres. Some of them have retained their function, while others have become rare or obsolete.
Keywords: dance; Grabar; Middle Armenian; Eastern Armenian; Western Armenian; word formation; root; suffix; compound words; neologisms